Pengaruh Iklan dan Brand Image Terhadap Daya Beli Konsumen pada PT Olagafood Industri - moh. alfanny nasution; Evalina Pakpahan (JURNAL MANAJEMEN DAN BISNIS, 2022)
This study aims to determine the effect of advertising on consumer purchasing power, determine the influence of Brand Image on consumer purchasing power and determine the effect of advertising and Brand Image on consumer purchasing power at Pt Olaga food Industri. This study quantitative description of the questionnaire instrument population of 43 consumers who make purchases In Independent Swayalan, determination of the sample using saturated samples so that the research sample. 43 people. The results of the study were the value of ad counting coefficient 4.772; value of ttable 2.018 then the value of ttable > ttable ( 4.772 > 2.018); value of sig < 0.05 (0.000 < 0.05), value of brand Image counting coefficient 2.473; value of ttable 2.018 then the value of ttable > ttable (2.473 > 2.018); value of sig < 0.05 (0.018 < 0.05). Value Fhitung advertising and Brand Image 32,660 and Ftable value 3,219 then Fhitung > Ftable (32,660 > 3,219); GIS value < 0,05 (0,000 < 0,05). The value of RSquare 0.620 or R2 x 100% 62.00%, meaning that the variable because it gives a big contribution to explain the purchasing power of consumers is 62.00% the remaining 38.00% is influenced by other factors. The conclusion of the study is the effect of advertising significance to the purchasing power of consumers, Brand Image significance to the purchasing power of consumers and simultaneously advertising and Brand Image significance to the purchasing power of consumers at Pt Olaga food Industri.